Late Neoliberalism: The Financialization of Homeownership and Housing Rights - Rolnik, Raquel (International journal of urban and regional research, 2013)
Over the last few decades we have witnessed a global U‐turn in prevailing housing and urban policy agendas, spread around the world by the driving forces of globalization and neoliberalism. The new paradigm was mainly based on the withdrawal of states from the housing sector and the implementation of policies designed to create stronger and larger market‐based housing finance models. The commodification of housing, together with the increased use of housing as an investment asset within a globalized financial market, has profoundly affected the enjoyment of the right to adequate housing. Taking the World Bank's 1993 manifesto as a starting point and the subprime crisis as its first great international flashpoint, this essay traces some key elements of the neoliberal approach to housing and its impact on the enjoyment of the right to housing in different contexts and times. The reform of housing policy — with all its components of homeownership, private property and binding financial commitments — has been central to the political and ideological strategies through which the dominance of neoliberalism is maintained. Conversely, the crisis (and its origins in the housing market) reflects the inability of market mechanisms to provide adequate and affordable housing for all.